Vibration Analysis of Non-Uniform Imperfect Functionally Graded Beams with Porosities in Thermal Environment. (9th October 2017) - Ebrahimi, F.; Hashemi, M.
Abstract : In the present study, thermo-mechanical vibration behavior of non-uniform beams made of functionally graded (FG) porous material are investigated under different thermal loadings for the first time. It is observed that during the fabrication of functionally graded materials (FGMs) porosities and micro-voids can be occured inside the material, thus in this study vibration analysis of FG beams by considering the effect of these imperfections is performed. Material properties of the FG beam are assumed to be temperature-dependent and vary continuously through thickness direction according to a power-law scheme which is modified to approximate material properties for both even and uneven distributions of the porosities. Different thermal environmental conditions, including uniform, linear and non-linear temperature changes through the thickness direction are considered. The motion equations are derived based on the Euler-Bernoulli beam theory through Hamilton's principle and they are solved applying the differential transformation method (DTM). In order to show the accuracy of the present analysis, comparisons are made with previous researches and an excellent agreement is observed. The obtained results are presented for the thermo-mechanical vibration characteristics of the FG beams such as the influences of various temperature rises, gradient index, porosity volume fraction, taper ratio and the boundary conditions in detail.